Pembelajaran Tari Sambut Seinggok Sepemunyian dengan Media Audio Visual di Kelas X MAN 1 Kota Prabumulih - Tara Alfeni; Muhamad Idris (Mahesa Research Center, 2023)
The application of the audio-visual method in learning has an important role, especially in the aspects of students' skills and practical activities. Learning the art of dance at MAN 1 Kota Prabumulih is to demonstrate traditional dance movements based on concepts, techniques, and procedures according to the count/beat. Learning the art of welcoming Seinggok Sepemunyian dance which is a typical dance of Prabumulih City. This study aims to determine the learning of the Seinggok Sepernunyian welcome dance with audio-visual media. This study used descriptive qualitative method. the process of implementing learning starts from the preparation, implementation and evaluation of learning that has been carried out properly. The stages that have been carried out by the teacher have been prepared to help the learning process. Judging from the process that has been carried out in this study, the results of the research data that have been carried out by researchers both through observation, interviews and documentation techniques when learning the Seinggok Sepemunyian welcome dance with audio-visual media by teachers and students have run optimally and effectively. The results of the analysis of the assessment in looking at the results of student tariff practices seen from wiraga, wirama, and wirasa obtained from the number of 30 students who have reached the KKM value of 75 and the average value of students is 88. This value has reached the KKM that has been set by the school, so from the results of the evaluation can be stated that the students of class X IA 1 MAN 1 Prabumulih City have high creativity.